Exploring the influence of health management processes on health outcomes among internally displaced persons (IDPs) - Winifred Ekezie; Penelope Siebert; Stephen Timmons; Rachael L. Murray; Manpreet Bains (Elsevier, 2022)
Background: Despite global action and policy initiatives, internally displaced persons (IDPs) experience poor living conditions and lack healthcare access compared to refugees. This study sought to understand the relationship between health management processes and health outcomes among camp-dwelling IDPs in northern Nigeria. Method: 73 individuals participated in either a focus group (n = 49) or one-to-one interview (n = 24), comprising IDPs (n = 49), camp managers (n = 9), health workers (n = 7) and government administrative authorities (n = 8). Interviews explored IDP health management processes, partners and perceptions around camp management. Data were analysed using an inductive thematic approach. Results: Four main themes were identified: opinions about healthcare organisation and management, service availability, interventions and information management, and IDP health outcomes. Though many stakeholders, partnerships, and national and international government agencies were involved in the provision of healthcare services, respondents described efforts as disjointed. Reports suggested that the coordination and management of health services and resources were not tailored to the needs of those living in all camps. And because so many national and international agencies were involved, but under weak coordination, access to services was less than optimal and adequate management of critical public health interventions was lacking. Varied allocation of resources such as funding, medication and medically trained staff were viewed as key factors in the availability and the ability to access what was considered as essential healthcare services. Conclusion: The health of IDPs in camp-like settings was compromised by uncoordinated management, treatment, and control of communicable and non-communicable diseases. Government authorities need to be aware and consider the complexity of the multiagency involvement in the management and provision of IDP healthcare services. Introducing systems to streamline, monitor and support IDP healthcare management could be cost-effective strategies for achieving optimal health care.